2021
DOI: 10.3389/feduc.2021.643221
|View full text |Cite
|
Sign up to set email alerts
|

Colliding Identities During COVID-19: Identifying and Addressing the Challenges of Being an Academic Mother During a Global Pandemic

Abstract: Academic workloads require a careful balance of teaching, research, supervision, and administrative responsibilities. Being an academic parent adds an additional level of responsibility to this, which has traditionally been successfully managed with organisation, careful planning and support. For many academic parents the Covid-19 pandemic disrupted this carefully curated balance, forcing them to work from home while also dealing with the loss of childcare and the requirement to provide homeschooling. The pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
(18 reference statements)
1
2
0
Order By: Relevance
“…One likely explanation for this is that during COVID-19 women assumed increased care-giving and home-schooling responsibilities as childcare and schools were shut down during the pandemic. This conclusion is supported by the literature on the division of childcare between women and men [( 14 , 15 ); also see ( 16 )]. Thus, long-term investments in and promotion of gender equality are still needed, and if left unaddressed, could reverse or stall the gains made by women over the past several decades.…”
supporting
confidence: 66%
“…One likely explanation for this is that during COVID-19 women assumed increased care-giving and home-schooling responsibilities as childcare and schools were shut down during the pandemic. This conclusion is supported by the literature on the division of childcare between women and men [( 14 , 15 ); also see ( 16 )]. Thus, long-term investments in and promotion of gender equality are still needed, and if left unaddressed, could reverse or stall the gains made by women over the past several decades.…”
supporting
confidence: 66%
“…After realising Covid‐19 was not ‘just a flu’ (Van Prooijen et al, 2022), scholarly attention started to engage with its consequences on various areas of life, such as healthcare and employment, as well as focusing on children's experiences around the world. This literature developed across two major themes: the effects of Covid‐19 on children's education (Castro‐Kemp & Mahmud, 2021; Crane et al, 2021; Kim et al, 2021; Scott et al, 2021; Spadafora et al, 2022; and others); and its impacts on family dynamics (Chen et al, 2021; Harrop, 2021; Limbers & Pavlov, 2021; and others). A third line of enquiry has developed to consider the emotional and mental health issues brought about by isolation and social distancing in children and adolescents (Chen et al, 2020; Crane et al, 2021; Egan et al, 2021; He & Li, 2021; Linnavalli & Kalland, 2021; O'Keefe et al, 2021; Sabaoui et al, 2021; Tebet et al, 2021; Wang et al, 2021; and others).…”
Section: The Impacts Of Covid‐19 On Children: Where Are the African C...mentioning
confidence: 99%
“…Mothers were disproportionately affected by school closures, and loss of childcare and social support. It has been extensively reported that mothers shouldered the bulk of unpaid domestic work, even when their partner worked from home (e.g., Daniela et al, 2021 ; Harrop, 2021 ; Meraviglia and Dudka, 2021 ). The home-schooling and steep increase in caring responsibilities during the lockdowns put mothers at risk of poor mental health and wellbeing (e.g., Taylor et al, 2021 ; Racine et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%